2021
DOI: 10.1016/j.lanwpc.2020.100086
|View full text |Cite
|
Sign up to set email alerts
|

HIV non-occupational post-exposure prophylaxis (nPEP) awareness and promotion among five key populations in China: A cross-sectional study

Abstract: Background: This study investigated HIV non-occupational post-exposure prophylaxis (nPEP) awareness and promotion, and related sociodemographic and behavioural factors among five key populations in China.Methods: From November 2018 to September 2019, we adopted convenience sampling to recruit participants who were age ≥ 18, self-reported HIV status as either negative or unknown and provided informed consent from five key populations cross-sectionally in 10 Chinese cities. Univariable and multivariable logistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
3
2
Order By: Relevance
“…This study is the first to look at PEP and PrEP knowledge and use outside the MSM community and adds to the body of evidence of these subjects in Europe. Low percentages of knowledge and use of both prevention tools were also found among key populations in both the United States (20) and China (21), although the use of both tools in our sample is lower than that reported in those studies.…”
Section: Discussioncontrasting
confidence: 81%
“…This study is the first to look at PEP and PrEP knowledge and use outside the MSM community and adds to the body of evidence of these subjects in Europe. Low percentages of knowledge and use of both prevention tools were also found among key populations in both the United States (20) and China (21), although the use of both tools in our sample is lower than that reported in those studies.…”
Section: Discussioncontrasting
confidence: 81%
“…The frequency of consistent condom use in this study was higher than that reported in similar studies conducted in China10 15 and other countries 13 16. This could have been owing to the high level of HIV knowledge and awareness of partners’ infection status, both of which are related to less-risky sexual behaviours 12 17 18.…”
Section: Discussioncontrasting
confidence: 75%
“…Without an internet medical platform, individuals have to first recognize their potential risk of exposures, make decisions on seeking PEP service with great uncertainty, find the designated hospitals, visit the hospital during its working hours, get prescription from doctors, and obtain medicines; importantly, all of these activities should be completed within 72 hours of exposure, reflecting the inherent limitations of PEP service [ 19 , 46 ]. Moreover, as the effectiveness of PEP largely depends on timeliness of regimen initiation, to better improve the online PEP service model, future educational campaigns should focus more on ways to shorten the time from exposure to decision making on PEP use, to help patients initiate PEP treatment as early as possible because this not only helps reduce anxiety and fear among patients, but also is beneficial to ensure effectiveness of the therapeutic prevention.…”
Section: Discussionmentioning
confidence: 99%
“…As a biomedical HIV prevention strategy, nonoccupational HIV postexposure prophylaxis (PEP) has been proven to be a safe and effective strategy aimed at preventing HIV among those with a recent HIV exposure [10][11][12][13]. Currently, PEP has been widely implemented in many countries [14][15][16][17]; however, it remains an underutilized prevention strategy in China [18,19]. Between 2018 and 2019, the National Center for AIDS/STD Control and Prevention, Chinese Center for Disease Control and Prevention (NCAIDS, China CDC) carried out a pilot program of PEP among MSM in 7 provinces to promote the uptake of PEP and preexposure prophylaxis (PrEP) [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation